Utility values for specific chronic myeloid leukemia chronic phase health states from the general public in the United Kingdom. Issue 8 (August 2014) - Guest, Julian F.; Gray, Elizabeth J.; Szczudlo, Tomasz; Magestro, Matthew
Abstract This study elicited time trade-off (TTO) and standard gamble (SG) preference values associated with four health states corresponding to response levels in chronic phase chronic myeloid leukemia (CML) from members of the general public in the UK (n = 235). Health states studied were treatment-free remission (TFR), complete molecular response (CMR, i.e. undetectable disease on treatment), molecular response and reappearance of detectable disease (i.e. relapse from TFR to molecular response requiring treatment). TFR was the most preferred health state (mean utility of 0.97 [TTO] and 0.87 [SG]) followed by CMR (mean utility of 0.96 [TTO] and 0.85 [SG]) followed by molecular response (mean utility of 0.94 [TTO] and 0.80 [SG]) followed by reappearance of detectable disease (mean utility of 0.90 [TTO] and 0.72 [SG]). SG values were significantly lower than TTO values (p < 0.001). The study demonstrated that different treatment responses may impact on the health-related quality of life of patients with chronic phase CML.